2006
DOI: 10.1016/j.cellbi.2005.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Repercussions of castration and vasectomy on the ductal system of the rat ventral prostate

Abstract: Diseases, such as cancer and benign prostatic hyperplasia, are related to disruption of the mechanism regulating the balance between cell proliferation and apoptosis in prostatic cells. Since castration and vasectomy might alter that balance, this study evaluates the cell proliferation, apoptosis and height of the secretory epithelium of the ventral-prostate ductal system post-castration and vasectomy. Immunohistochemical (PCNA and Ki67), cytochemical (Fuelgen reaction) and morphometric investigation have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 30 publications
3
14
3
Order By: Relevance
“…Other studies also show that the increase of apoptosis in response to androgen deprivation occurs predominantly in the ventral lobe (Banerjee et al, 1995(Banerjee et al, , 2000. Nevertheless, the increase of the apoptotic index detected in the present study was less than that observed by other authors (Garcia-Florez et al, 2005;Pereira et al, 2006). This difference might be explained by several circumstances: (a) the different stage of development of the animals (peripubertal versus adult); (b) the different model of androgen deprivation (androgenic blockade versus surgical castration).…”
Section: Discussioncontrasting
confidence: 86%
See 4 more Smart Citations
“…Other studies also show that the increase of apoptosis in response to androgen deprivation occurs predominantly in the ventral lobe (Banerjee et al, 1995(Banerjee et al, , 2000. Nevertheless, the increase of the apoptotic index detected in the present study was less than that observed by other authors (Garcia-Florez et al, 2005;Pereira et al, 2006). This difference might be explained by several circumstances: (a) the different stage of development of the animals (peripubertal versus adult); (b) the different model of androgen deprivation (androgenic blockade versus surgical castration).…”
Section: Discussioncontrasting
confidence: 86%
“…However, Kim et al (2002) found diminution in cell proliferation evidenced by immunostaining for Ki-67 in castrated rats with implants of prostate cancer cell lines. The differences were remarkable when comparing our PCNA results with those from other studies, because in surgically castrated and/or estrogen-treated adult rats, the index of PCNA-positive cells decreased significantly according to other authors (Garcia-Florez et al, 2005;Pereira et al, 2006). These discrepancies could be either due to the stage of the development of the animals (prepubertal versus adult), the model of androgen deprivation (pharmacological versus surgical castration), or the methodology employed for counting cells.…”
Section: Discussioncontrasting
confidence: 50%
See 3 more Smart Citations